It is currently 18 Oct 2017, 17:39

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

OG Pg 186 Problem 245

Author Message
Current Student
Joined: 03 Dec 2007
Posts: 83

Kudos [?]: 6 [0], given: 0

Schools: NYU STERN
OG Pg 186 Problem 245 [#permalink]

Show Tags

18 Jan 2009, 13:07
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Ok so I feel stupid asking this but i am having a problem at a certain point in the problem:

If x+y=a and x-y=b then 2xy= ?

The answer is: 2xy= (a^2 - b^2)/2

I got it to this:

y= [2a/2] - [(a+b)/2]

why is the numerator then in the next step: 2a-a-b and not 2a-a+b?

Thanks!

Kudos [?]: 6 [0], given: 0

Director
Joined: 12 Jul 2008
Posts: 514

Kudos [?]: 162 [1], given: 0

Schools: Wharton
Re: OG Pg 186 Problem 245 [#permalink]

Show Tags

18 Jan 2009, 15:00
1
KUDOS
hardaway7 wrote:
Ok so I feel stupid asking this but i am having a problem at a certain point in the problem:

If x+y=a and x-y=b then 2xy= ?

The answer is: 2xy= (a^2 - b^2)/2

I got it to this:

y= [2a/2] - [(a+b)/2]

why is the numerator then in the next step: 2a-a-b and not 2a-a+b?

Thanks!

hardaway, when you post the question, you don't need to post page number and problem number from OG. Just copy the question w/ all the choices.

$$(x+y)^2 = x^2 + 2xy + y^2$$
$$(x-y)^2 = x^2 - 2xy + y^2$$

we know that:
$$a^2 = (x+y)^2$$
$$b^2 = (x-y)^2$$

so,
$$a^2 - b^2 = (x^2 + 2xy + y^2) - (x^2 - 2xy + y^2)$$
$$= x^2 - x^2 + 2xy + 2xy + y^2 - y^2$$
$$= 4xy$$

$$4xy = a^2 - b^2$$
$$2xy = (a^2 - b^2)/2$$

Kudos [?]: 162 [1], given: 0

Re: OG Pg 186 Problem 245   [#permalink] 18 Jan 2009, 15:00
Display posts from previous: Sort by